THE EDUCATIONAL POINT OF THE “NUSSA THE MOVIE” ANIMATION MOVIE PRODUCTION BY BONY WIRASMONO - Nidia Sulistyowati; Syalwa Bella Sopian; Irma Rasita Gloria Barus; Ira Resmayasari (Pusat Riset dan Inovasi Nasional, 2022)
The film